2004
DOI: 10.1002/pssc.200404845
|View full text |Cite
|
Sign up to set email alerts
|

Do we really need another PL study of CuInSe 2 ?

Abstract: A detailed composition, intensity and temperature dependent photoluminescence (PL) study of CuInSe 2 has been performed to obtain data on defects, directly comparable to the defects in CuGaSe 2 , prepared under the same conditions. Epitaxial films are grown by metal organic vapour phase epitaxy on GaAs. The PL study reveals three shallow defects, which are responsible for the doping behaviour in CuInSe 2 : two acceptors, 40 and 60 meV deep, and a donor, approximately 12 meV deep. The shallower acceptor dominat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
64
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 24 publications
(28 reference statements)
11
64
1
Order By: Relevance
“…PL studies of Cu-rich CIS absorbers find three different energies for the doping defects in CIS. A ∼ 10 meV donor and additional to that three acceptor levels: for near stoichiometry one with an E A of 40 meV (labelled 'A1'), for Cu-rich of 60 meV ('A2') [21] and a third one at 100 meV independent of Cu-excess ('A3' in [22]). These are well within the measured energy range, the best explanation of step 2 therefore might be the freeze-out of either 'A2', 'A3', or both together.…”
Section: Measurement Resultsmentioning
confidence: 99%
“…PL studies of Cu-rich CIS absorbers find three different energies for the doping defects in CIS. A ∼ 10 meV donor and additional to that three acceptor levels: for near stoichiometry one with an E A of 40 meV (labelled 'A1'), for Cu-rich of 60 meV ('A2') [21] and a third one at 100 meV independent of Cu-excess ('A3' in [22]). These are well within the measured energy range, the best explanation of step 2 therefore might be the freeze-out of either 'A2', 'A3', or both together.…”
Section: Measurement Resultsmentioning
confidence: 99%
“…Data from sample IEC-1 is further analyzed in the following and is shown in Figure 2 Above 40 K, there is a slight redshift (~0.4-0.7 meV/10 K) in peak positions with increasing temperature, possibly due to thermal expansion. Typically, a donor-acceptor pair (DAP) emission will become a free-to-bound (FB) emission as temperature increases because the shallower of the two defects involved in the DAP emission will thermally empty [22]. This is normally marked by a noticeable blueshift in the peaks.…”
Section: Resultsmentioning
confidence: 99%
“…Compositiondependent PL measurements and Hall measurements have been performed on chalcopyrite CIGSe by Siebentritt et al [4,5] For example, close to the stoichiometric compound, PL measurements showed three acceptor levels with ionization energies of 40, 60, and 100 meV above the valence band maximum (VBM) and one donor level 10 meV below the conduction band minimum (CBM). [4] The intensities of these three peaks vary,…”
Section: Introductionmentioning
confidence: 99%